2018
DOI: 10.1016/s2213-2600(18)30006-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of exacerbation risk and response to budesonide in patients with chronic obstructive pulmonary disease: a post-hoc analysis of three randomised trials

Abstract: AstraZeneca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
315
2
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 349 publications
(347 citation statements)
references
References 24 publications
(26 reference statements)
19
315
2
11
Order By: Relevance
“…The INCONTROL study showed that for patients with blood-eosinophil counts ≥100 cells/µL, exacerbations were reduced significantly more with budesonide–formoterol compared with formoterol alone ( P =0.015) 42. The higher the blood-eosinophil count, the greater the exacerbation rate without ICSs and the greater the reduction in exacerbations with ICSs, which tends to reach a plateau around eosinophil counts of 400 cells/µL.…”
Section: Predictors Of Responsementioning
confidence: 99%
See 3 more Smart Citations
“…The INCONTROL study showed that for patients with blood-eosinophil counts ≥100 cells/µL, exacerbations were reduced significantly more with budesonide–formoterol compared with formoterol alone ( P =0.015) 42. The higher the blood-eosinophil count, the greater the exacerbation rate without ICSs and the greater the reduction in exacerbations with ICSs, which tends to reach a plateau around eosinophil counts of 400 cells/µL.…”
Section: Predictors Of Responsementioning
confidence: 99%
“…Differences in study populations could account for the disparate findings, as the INCONTROL study had a larger number of smokers with more exacerbations compared with the SPIROMICS cohort 42,48…”
Section: Predictors Of Responsementioning
confidence: 99%
See 2 more Smart Citations
“…However, improvements in lung function, exacerbation risk and all-cause mortality with ICS treatment when used in combination with long-acting beta-agonist (LABA) bronchodilators have been reported recently (7,8). In addition, some patients with COPD with no previous history of asthma can benefit from ICS, such as those with high blood eosinophil counts (9)(10)(11)(12)(13)(14). It has previously been shown that gene expression profiling in bronchial biopsies in COPD may identify those with asthma-COPD overlap, as reflected by a Th2-high inflammatory profile and a favorable shortand long-term ICS treatment response (3).…”
Section: Introductionmentioning
confidence: 99%